299 PRE-084, A Sigma-1 Receptor Ligand, Protects Against Excitotoxic Perinatal Brain Injury in Newborn Mice. (October 2012) - Griesmaier, E; Posod, A; Gross, MJ; Neubauer, V; Wegleiter, K; Hermann, M; Urbanek, M; Keller, M; KiechlKohlendorfer, U
Abstract : Background: Excessive glutamate release followed by N-methyl-D-aspartate receptor (NMDAR) activation displays an important cascade in the pathophysiology of perinatal brain injury. We have previously shown that dextromethorphan, a low-affinity NMDAR antagonist, is neuroprotective in an animal model of neonatal excitotoxic brain injury. Of interest, dextromethorphan also shows agonistic properties at the sigma-1 receptor (σ1R). Sigma-1 agonists have given beneficial results in animal models of adult brain injury. Aim of the study: To evaluate the effect of the selective σ1R agonist 2-(4-morpholinethyl) 1-phenylcyclohexanecarboxylate (PRE-084) in neonatal excitotoxic brain injury. Results: A single intraperitoneal injection of 0.1 µg/g (low dose) or 10 µg/g (high dose) bodyweight (bw) PRE-084, given 1 h after the excitotoxic insult, significantly reduced lesion size in cortical gray matter 24 h and 120 h after the insult. Repetitive injections of 0.1 µg/g PRE-084 proved to be equally effective. PRE-084 treatment resulted in a decrease in cell death indicated by reduced TUNEL positivity and caspase-3 activation. PRE-084 reduced the number of isolectin B4-positive, activated microglial cells. Quantitative real-time PCR analysis showed no effect on σ1R gene expression at 1, 4, 8, 12, 24 and 48 h after intracranial ibotenate injection compared to healthy controls. In vitro PRE-084 protected against glutamate-induced morphological and functional changes in primary hippocampal neurons. Conclusion: We demonstrate that systemic treatment with the highly selective σ1R agonist PRE-084 protects against NMDAR-mediated excitotoxic brain damage.